Effect of Sulphurization Process on Vitamin, Phytosterol and Fatty Acid Levels of Some Apricot Cultivars Grown in Turkiye - Kamisli, Fethi; Mutlu, Nazlı Gulum (My University, 2024)
Two kinds of fresh apricot (Prunus armeniaca L.) samples were sulphurized in various concentrations of sodium metabisulfite solution at different immersion times. The sulphur contents in fresh apricot samples and in the apricot samples dried in open air for a week were determined as a function of immersion time. Variations of vitamins of K1, D2, E and phytosterols were determined as a function of sulphur content of two kinds of fresh apricot samples. It was observed that amount of vitamins of K1, D2 and E decreased with increasing concentrations of sodium metabisulfite solution and prolonging immersion time. Moreover, it was observed that there was no regular relationship between sulfur content and phytosterol changes in both apricot samples. While fatty acids such as palmitic acid, myristic acid and oleic acid were determined in all apricot samples, the palmitoleic acid, stearic acid and arachidonic acid were encountered in some samples.
Keywords: Fatty acids; Apricot; vitamins; sulphurization; physterols